High Intestinal and Systemic Levels of Interleukin-23/T-Helper 17 Pathway in Chinese Patients with Inflammatory Bowel Disease - Lu Song; Rui Zhou; Sha Huang; Feng Zhou; Shufang Xu; Wei Wang; Fengming Yi; Xiaobing Wang; Bing Xia (Mediators of Inflammation)
Interleukin-23/T-helper 17 (IL-23/Th17) pathway plays a key role in the pathogenesis of inflammatory bowel disease (IBD), but little is known about its expression in Chinese population. In this study, we investigated the mRNA and protein levels of IL-12p40, tumor necrosis factor-like cytokine 1A (TL1A), Janus kinase 2 (JAK2), and IL-23R both locally and systemically in Chinese IBD patients. Our results indicated that the mRNA levels of IL-12p40 and TL1A were increased in ulcerative colitis (UC) patients. Furthermore, serum IL-12p40 and TL1A levels were higher in active UC patients, especially in patients with disease course less than 1.25 years or initial onset. No correlation was found between the genotype and serum levels of IL-12p40 or TL1A in UC patients. Additionally, the mRNA and protein expression of JAK2 and IL-23R were increased in UC and Crohn’s disease (CD) patients. Taken together, our results provided evidence that IL-23/Th17 pathway genes may represent important biomarkers of active stage of IBD and serve as novel therapeutic targets for IBD in Chinese population.